Synthesis of Allenyl Esters by Horner–Wadsworth–Emmons-Type Reactions of Methyl 2-[Bis(benzylthio)phosphoryl]acetate and Ketenes Using Grignard Reagents - Nakao, Michiyasu; Tabaru, Masakazu; Imai, Ayato; Kitaike, Syuji; Sano, Shigeki (Synlett, 2025)
Methyl 2-[bis(benzylthio)phosphoryl]acetate and its analogues have proven to be efficient Horner–Wadsworth–Emmons (HWE)-type reagents for synthesizing conjugated allenyl esters and their analogues through reactions with disubstituted ketenes using Grignard reagents. A series of HWE-type reagents containing the bis(benzylthio)phosphoryl group showed better reactivity than the corresponding HWE reagents, where two phosphorus–sulfur bonds were substituted with phosphorus–oxygen bonds.
Keywords: Horner–Wadsworth–Emmons reagents; Phosphorus–sulfur bond; Conjugated allenyl esters; Ketenes; Allenes; Grignard reagents; Olefination